The first cross-national study of adolescent young carers aged 15–17 in six European countries. (5th February 2023) - Lewis, Feylyn Mercedies; Becker, Saul; Parkhouse, Thomas; Joseph, Stephen; Hlebec, Valentina; Mrzel, Maja; Brolin, Rosita; Casu, Giulia; Boccaletti, Licia; Santini, Sara; D'Amen, Barbara; Socci, Marco; et al.
Abstract : For the first time, this article will provide a cross-national profile of adolescents who provide unpaid care to their ill or disabled family members in six European countries with varied levels of awareness, policy and service provision regarding adolescent young carers. Utilising an online survey, 2, 099 adolescent young carers were identified in Italy, the Netherlands, Slovenia, Sweden, Switzerland and the UK. This article focuses on the impact of unpaid care on their mental health, well-being, physical health and education. Their preferences for informal and formal support were also examined. These groundbreaking findings help promote a 'rights' approach to adolescent young carers, which can serve as a critical driver for supportive policy creation on both a country-specific and pan-European level.